reaper is required for neuroblast apoptosis during Drosophila development. - Peterson, C.; Carney, G.E.; Taylor, B.J.; White, K. (Development, 2002)
Developmentally regulated apoptosis in Drosophila requires the activity of the reaper (rpr), grim and head involution defective (hid) genes. The expression of these genes is differentially regulated, suggesting that there are distinct requirements for their proapoptotic activity in response to diverse developmental and environmental inputs. To examine this hypothesis, a mutation that removes the rpr gene was generated. In flies that lack rpr function, most developmental apoptosis was unaffected. However, the central nervous systems of rpr null flies were very enlarged. This was due to the inappropriate survival of both larval neurons and neuroblasts. Importantly, neuroblasts rescued from apoptosis remained functional, continuing to proliferate and generating many extra neurons. Males mutant for rpr exhibited behavioral defects resulting in sterility. Although both the ecdysone hormone receptor complex and p53 directly regulate rpr transcription, rpr was found to play a limited role in inducing apoptosis in response to either of these signals.